Immunogenicity of peptide‐based vaccine composed of epitopes from Echinococcus granulosus rEg.P29. Issue 4 (27th February 2023) - Lv, Yongxue; Chang, Liangliang; Yang, Jihui; Wen, Jia; Zhao, Yinqi; Zhu, Mingxing; Wu, Changyou; Zhao, Wei
Abstract: Echinococcus granulosus is one of the main causes of economic loss in the livestock industry because of its food‐borne transmission. Cutting off the transmission route is a valid prevention method, and vaccines are the most effective means of controlling and eliminating infectious diseases. However, no human‐related vaccine has been yet marketed. As a genetic engineering vaccine, recombinant protein P29 of E. granulosus (rEg.P29) could provide protection against deadly challenges. In this study, we generated peptide vaccines (rEg.P29T, rEg.P29B, and rEg.P29T+B ) based on rEg.P29 and an immunized model was established by subcutaneous immunization. Further evaluation showed that peptide vaccine immunization in mice induced T helper type 1 (Th1)‐mediated cellular immune responses, leading to high levels of rEg.P29 or rEg.P29B ‐specific antibodies. In addition, rEg.P29T+B immunization can induce a higher antibody and cytokine production level than single‐epitope vaccines, and immune memory is also longer. Collectively, these results suggest that rEg.P29T+B has the potential to be developed as an efficient subunit vaccine for use in areas where E. granulosus is endemic. Abstract : Peptide vaccine immunization in mice induced Th1‐mediated cellular immune responses, leading to high levels of rEg.P29 or rEg.P29B ‐specific antibodies. rEg.P29T+B immunization induced more memory cells to produce.